Acoustic emission during the millisecond laser-optical glass interaction assisted by the nanosecond laser - Y. Pan (AIP Advances, 2018)
A hydrophone is used to detect the acoustic emission for the combined pulsed laser (CPL)-BK7 glass interaction. The CPL is composed of a nanosecond (ns) laser and a millisecond (ms) laser, which are separated with a certain period of time. Owing to the material defects affected mechanism, fluctuations are observed for the transmission time and the intensity of the acoustic emission during the ns laser interaction period. A weak and a strong acoustic emissions with spectrums dominated in the ranges of 10kHz∼60kHz and less than 8kHz, respectively, are detected during the remaining millisecond laser irradiation period. The two different behaviors of the acoustic emission are analyzed together with the evolution of the plume emission captured by the high speed camera during the laser irradiation and the ablated morphology on the sample. Results show that the high-frequency acoustic signal arises from a weak interaction process that a short lifetime plume emission and a shallow pit at the sample surface are observed. While the low-frequency acoustic signal is associated with a strong interaction process that an intense plume emission and a conical shaped cavity are detected. The consistent behaviors for the acoustic emission, the plume emission and the ablated size in dependence on the delay make the acoustic signal detection a reliable method in monitoring the CPL-BK7 glass interaction process and estimating the ablation results.